Reclaiming the Night-Time Economy - Fileborn, Bianca (Palgrave Macmillan UK, 2016)
Keywords: Alcohol; Assemblage; Camille; Community; Crime prevention; Criminology; Culture; Drugs; Environmental design; Gender; LGBTIQ; Licensed venues; Safety; Sexual consent; Sexual ethics; Sexual offending; Sexual violence; Sexuality; Space; Young people

Swedish music festival to go 'women-only' following string of sexual assaults - White, Adam (The Telegraph, 2017)
Sweden's biggest music festival will be replaced next year by a women-only alternative after reports of a series of rapes and sexual assaults at this year's event.
Keywords: Crime; Culture; Music; Skepta; Standard; Sweden